PENGARUH GAYA BELAJAR DAN MINAT BELAJAR TERHADAP KEMAMPUAN BERPIKIR KREATIF SMP KELAS VIII - Ginting, Grace Sabatini Br; Saija, Louise M (Jurnal Padegogik, 2025)
The main purpose of this study was to determine whether there is an effect of learning style and interest in learning on the creative thinking ability of 8th grade junior high school students. Creative thinking ability is the ability to think consistently to produce something creative. While, learning style is a fixed way for students to receive information, remember, and think to solve a problem, and interest is an internal drive that causes attention, interest, and satisfaction in an activity. This research was conducted using a quantitative approach with a descriptive correlational research design. Respondents in this study were 78 students from classes VIIIF and VIIIG SMPN 1 Parongpong, west Bandung. The instruments used were questionnaires for learning style and for learning interest, and a creative thinking ability test. The research result shows that: (1) There are 22 students with one dominant learning style, 46 students have two, 60 students have three dominant learning styles, and there are more students with group learning style; (2) the learning interest of junior high school students are in the medium category, (3) 16.67% of the students have high categorical creative thinking ability, 62.82% of the students have medium, and 20.51% of the students have low categorical creative thinking ability; (4) There is an effect of learning style and learning interest towards the creative thinking ability of grade eight junior high school students.